XML semantics extension - Havasi, Ferenc (Acta Cybernetica, 2002)
Nowadays one of the best standards for storing structured data is XML. The key idea behind our paper is based on a relationship between XML documents and attribute grammars. This parallel makes it possible to apply techniques of attribute grammars (semantics rules) to the XML environment. We present a new method for extending XML. After a background discussion we formally introduce a way of defining real XML attributes using semantics rules. This allows us to incorporate semantics rules into XML files in such a way that it does not violate the original XML specification and is suitable for compressing using learning. After learning an associated semantics rule file preserves the relationship between attributes.